Female reproductive hormones and biomarkers of oxidative stress in genital chlamydia infection in tubal factor infertility (2015)
Background: Genital Chlamydia infection (GCI) and the associated pathologies have been implicated in tubal infertility. Though the actual pathologic mechanisms are still uncertain, oxidative stress and other factors have been implicated. The purpose of the study was to determine the possible contribution of female reproductive hormones and biomarkers of oxidative stress in genital Chlamydial infection to tubal occlusion. Methods: This prospective case control study was carried out by recruiting 150 age matched women grouped into infertile Chlamydia positive women (n=50), fertile Chlamydia positive women (n=50) and fertile Chlamydia negative women as controls (n=50). High vaginal swabs and endocervical swabs were collected for screening Neisseria gonorrhoeae, Chlamydia trachomatis, Trichomonas vaginalis, Treponema pallidum, Staphylococcus aureus, and Candida albicans. Sera were collected for estimation of Chlamydia trachomatis antibody, female reproductive hormones [Follicle Stimulating Hormone (FSH), Luteinizing Hormone (LH), Oestradiol (E2), Progesterone (P4), Prolactin (PRL)] and biomarkers of oxidative stress [Total Antioxidant Capacity (TAC) and 8-hydroxyl-2-deoxyguanosine (8-OHdG)] by enzyme immunoassay (EIA). Data were analyzed using chi square, analysis of variance and LSD Post hoc to determine mean differences at p=0.05. Results: Among women with GCI, higher levels of LH and 8-OHdG were observed in infertile Chlamydia positive women compared to fertile Chlamydia positive women (p<0.05). Higher levels of LH and 8-OHdG and lower TAC levels were observed in infertile Chlamydia positive women compared to fertile Chlamydia negative controls (p<0.05). Conclusion: Mechanisms including oxidative DNA damage and reduced antioxidant capacity may be involved in the pathology of Chlamydia induced tubal damage.